If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -5b = -9 Combine like terms: 2b + -5b = -3b -3b = -9 Solving -3b = -9 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-3'. b = 3 Simplifying b = 3
| (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 | | 9-ln(4-x)=0 | | 4x=-5+2x+18 | | -2(-9w+1)-2w=2(w-1)-2 | | 2x+13=5x-14 | | 5y=2(y+6) | | -5w+3(w-5)=-13 | | 3*2-y=9 | | 3*3-y=9 | | 4x=8+3x | | 2b^4+8b^3+8b^2=0 | | 5+4D=47 | | 6(6v+5)=1+6v | | 7x+6=9x+x | | 250+.10y=350 | | x^2+y^2+30x-2y+210=0 | | 8.5X=11 | | x+.10y=350 | | 600+600= | | 5(x+5)=-5(2x-3)+x | | 23+6y-15=62 | | 5y=x+19 | | 189s=99+10 | | 7x-18=9x+4 | | 5(y-2)=-5y+40 | | 10x=4y+16 | | -c^2-5c+66= | | 3u+37=-5(u+9) | | 10x+x-4x= | | 5x-3-x=14-3x+11 |